Integration Of Active Games Into Pedagogical Models To Enhance University Students' Motivation For Physical Activity - Ruzieva Mahliyo Kayumovna (Next Scientists International Journal EIJP, 2026)
The article examines the integration of active games into pedagogical models to increase university students' motivation for physical activity. In the context of declining physical activity levels among youth, particularly in university settings, innovative approaches such as gamification and game-based learning models are highly relevant. Based on an analysis of scientific literature and empirical data, it is demonstrated how active games, integrated into the Teaching Games for Understanding (TGfU) and Sport Education (SE) models, contribute to increased intrinsic motivation, reduced amotivation, and improved student engagement. The study involved 72 university students divided into an experimental group using gamification and a control group with traditional methods. Results indicate a significant increase in intrinsic motivation (p < 0.01) and a decrease in amotivation (p = 0.010) in the experimental group. Pedagogical strategies, including the use of digital tools such as ClassCraft, and their impact on students' psychological needs according to self-determination theory are discussed. The article provides recommendations for implementing such models in university physical education programs, contributing to sustainable development goals in education, while considering regional features of Uzbekistan and contributions from local authors in the development of physical culture.